(untitled) (International Journal of Engineering and Computer Science, 2017)
is paper illustrate about cloud computing. Cloud computing is the use of computing resources (hardware and software) that are delivered as a service over a networks (typically the Internet). The name comes from the use of a cloud-shaped symbol as an abstraction for the complex infrastructure it contains in system diagrams. Cloud computing entrusts remote services with a user’s data, software and computation. Cloud computing relies on sharing of resources to achieve coherence and economies of scale similar to a utility (like the electricity grid) over a network.At the foundation of cloud computing is the broader concept of converged infrastructure and shared services.